More Than Instrument: Phenomenon of Valiha - Frąckowiak, Marcel (Interdisciplinary Studies in Musicology, 2026)
This article discusses the valiha, a Malagasy tube zither, recognizing it as an anthropological phenomenon – posthumanistically speaking – relational. The valiha, Madagascar’s traditional and par excellence national musical instrument, is not merely an organological object constituting the material heritage of the Malagasy people. As a human creation, the instrument is not simply a carrier of knowledge about its culture, but an active participant in it, organizing human experience within the framework of social practices related to the transmission of ancestral tradition and adaptation in processes of global changes. Transformations in construction, tuning, and the instrument’s function are linked to stabilizations and transformations of social attitudes and values. Inspired by posthumanisms, the article transcends the mind-body and culture-nature divides to rethink the relationship between human and matter. The analysis covers the ontology of the musical instrument, its anthropological-organological evolution, its agency in shaping Malagasy music and identity, and valiha’s multidimensional instrumentality – musical, cognitive, social, and transcendental.